2015
DOI: 10.1021/acs.jnatprod.5b00344
|View full text |Cite
|
Sign up to set email alerts
|

hERG Channel Inhibitory Daphnane Diterpenoid Orthoesters and Polycephalones A and B with Unprecedented Skeletons from Gnidia polycephala

Abstract: The hERG channel is an important antitarget in safety pharmacology. Several drugs have been withdrawn from the market or received severe usage restrictions because of hERG-related cardiotoxicity. In a screening of medicinal plants for hERG channel inhibition using a two-microelectrode voltage clamp assay with Xenopus laevis oocytes, a dichloromethane extract of the roots of Gnidia polycephala reduced the peak tail hERG current by 58.8 ± 13.4% (n = 3) at a concentration of 100 μg/mL. By means of HPLC-based acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 37 publications
(66 reference statements)
3
19
0
Order By: Relevance
“…External assistance by microbial endophytes cannot be excluded, as already addressed in our Primula studies [14]. In this context, the parallels of occurrence of oxepinelike structures in both Thymeleaceae [10] and Primula species [14] is a striking feature deserving closer attention.…”
mentioning
confidence: 74%
“…External assistance by microbial endophytes cannot be excluded, as already addressed in our Primula studies [14]. In this context, the parallels of occurrence of oxepinelike structures in both Thymeleaceae [10] and Primula species [14] is a striking feature deserving closer attention.…”
mentioning
confidence: 74%
“…Following this approach several authors have identified new compounds from vegetal sources in recent years. With the help of ESI-TOF or ESI-Q-TOF, as complementary technique, several classes of new compounds have been characterized including nortriterpenoids [77], unsaturated cyclic ketones [78], daphnane diterpenoid orthoesters and polycephalones [79], sesquiterpenes [80] and bisbibenzyls [81]. Using Orbitrap and LTQ-Orbitrap the exact mass of new compounds, such as triterpenoinds [59], cleordane diterpenoids [82], β-Dihydroagarofuran derivatives [83] and isoflavonoids [84] have been also determined.…”
Section: Esimentioning
confidence: 99%
“…reduced the hERG channel current by 50.4% and 58.8%, respectively. 69 , 70 From the latter plant material, it is the first time that diterpenes – in this case daphnane-type diterpenoid orthoesters ( 1–3 ) – were identified as hERG channel blockers. …”
Section: Approaches For the Identification Of Herg Channel Blockers Omentioning
confidence: 99%